The Effect of Different Rootstocks and Superphosphate Fertilizer on Growth and Leaf Phosphorus in Young ‘Lisbon’ Lemon Trees. - FAHMY, IBRAHIM; HASSABALLA, ISSAM A. (The Libyan Journal of Agriculture, 2023)
Plants of ‘Prior Lisbon’ lemon budded on four different rootstocks were set in the field in a randomized block experiment. All trees were maintained under a uniform N and K fertilizer ratio with five different levels of P. By the end of the third growing season in the field, the different P level treatments showed no response in trunk area or in leaf phosphorus percentage of the lemon scions. The mean percentage of leaf phosphorus in trees which received no superphosphate fertilizer during the three-year period after setting in the field was 0.151, being within the known optimum range. These practically invariable results were probably due to the beneficial effects of mixing organic matter with the soil in preparing the holes before transplanting. Meanwhile, the different rootstocks influenced significantly the tree growth and the phosphorus concentration of the lemon leaves. On the average, measurements of stem cross-sectional area showed that tops on rough lemon or on ‘Rangpur’ lime were more vigorous than on sour orange, while ‘Cleopatra’ mandarin was slow in growth. The latter supplied more phosphorus to the leaves of lemon scions than sour orange, rough lemon and ‘Rangpur’ lime being intermediary in this effect.